2015
DOI: 10.1136/bcr-2015-209906
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic change in a young woman's perception of her diabetes and remarkable reduction in HbA1c after an individual course of Guided Self-Determination

Abstract: A 24-year-old woman with type 1 diabetes participated in a randomised controlled trial proving effectiveness of a flexible Guided Self-Determination (GSD) intervention. She had for 10 years been living with a complex situation of eating disorder, poor glycaemic control, non-attendance and psychosocial distress. She managed to change her perception of diabetes dramatically and improved her glycaemic control. Considering the complexity of her case, we explored how she achieved these changes. A GSD-trained nurse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 20 publications
(16 reference statements)
0
15
0
Order By: Relevance
“…This interpretation is consistent with a recently published qualitative paper evaluating how a GSD approach could bring about a dramatic change in a young woman’ s perception of her diabetes. 21 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This interpretation is consistent with a recently published qualitative paper evaluating how a GSD approach could bring about a dramatic change in a young woman’ s perception of her diabetes. 21 …”
Section: Discussionmentioning
confidence: 99%
“… 19 20 In addition, a case report on a young woman showed considerable reduction in HbA 1c after a GSD intervention. 21 In conclusion, GSD seems worthy of further research for several reasons. First, patient involvement and person-centred care are highly appreciated and recommended, but difficult to implement as part of clinical care.…”
Section: Introductionmentioning
confidence: 97%
“…At the same time, studies have suggested a possible risk of not identifying patients’ needs because of the limited time allotted 13,14. Research has clarified that the relationship between patients with diabetes and HCPs was central for patients’ ability to cope with their disease 15,16. In particular, patients with cancer need supportive and caring relationships with the HCP17,18 because cancer treatment often affects patients’ quality of life, even years after the diagnosis 19.…”
mentioning
confidence: 99%
“… 31 Moreover, in previous research showing that the GSD intervention can develop life skills and reduce psychosocial distress in individuals with type 1 diabetes, participants completed the reflection sheets on paper at home as preparation for an in-person consultation with health care personnel, which may facilitate dialogue around assistance with, explanation for, and tailoring of the intervention. 13 19 The fact that the written reflection and communication with health care personnel occurred primarily electronically may have undermined perceptions of support for some participants.…”
Section: Discussionmentioning
confidence: 99%